FLUTUAÇÃO POPULACIONAL DE ALGUNS CALLIPHORIDAE (DIPTERA) EM POMAR DE GOIÂNIA, GOIÃS, BRASIL - Santos, Benedito Baptista dos; Ferreira, Maria Judy de Mello; Cunha, Hélida Ferreira da (REVISTA DE AGRICULTURA, 2015)
FLUTUAÇÃO POPULACIONAL DE ALGUNS CALLIPHORIDAE (DIPTERA) EM POMAR DE GOIÂNIA, GOIÃS, BRASIL